AN ANALYSIS OF CODE MIXING USED ON GITA SAVITRI'S YOUTUBE CHANNEL - Khairinnahda, Fitra; Delfi, Syofia; Eliwarti, Eliwarti (TELL - US JOURNAL, 2024)
Sociolinguistic is an interdisciplinary field of science that studies language in relation to the use of that language in society. The process of communication in which two languages used together by the speakers, sociolinguistics experts call it code mixing. Code-mixing is the use of two or more languages to interact with speakers in situations that require mixing the code. This research aims to discover the types and reasons of code-mixing used in the Gita Savitri YouTube channel. In this study, the writer used qualitative research design in the descriptive form. The results reveal 164 data of code-mixing. The first video, with the title ”Jadi Kaum Open-Minded,” with a total of 92 data, contains intra sentential and intra-lexical code mixing; the second video, with the title “Pengen Jago Bahasa Inggris,” with a total 44 data code mixing, contains intra sentential and intra lexical code mixing. The last video the titled “Memahami Tone Policing: Taktik Membungkam Suara Yang Terpingirkan,” a total of 28 data containing intra-sentential and intra-lexical code mixing. The writer found the reasons for code mixing: talking about a particular topic, repetition used to clarify, and being emphatic about something in three videos. In summary, findings indicate that the three videos on Gita Savitri’s YouTube channel have a lot of code-mixing for viewers to know this phenomenon with the most significant number being in the video with the title “Jadi Kaum Open-Minded”.Keywords: analysis,code mixing, types of code mixing, reasons for code mixing